Analisis Korelasi Disaster Resilience dengan Faktor Ansietas Tenaga Kesehatan Tim PSC 119 yang terlibat dalam Manajemen Bencana - Risa Herlianita; Indri Wahyuningsih; Muhammad Wildan Al Furqoni; Alami Nurhandarbeni (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Disaster resilience leads to the capacity that individuals have to adapt positively in the face of disasters. The purpose of this study is the Development of a Disaster Resilience Model in an Effort to Improve the Disaster Resilience of Health Workers The PSC 119 Team involved in Disaster Management with the first stage of analyzing factors related to disaster resilience in the PSC 119 team involved in handling natural disasters. The research design used by researchers is correlational research with a cross-sectional approach. In this study will use the Purposive sampling technique. The sampling technique uses a total sampling and collected as many as 110 PSC 119 officers in Malang Regency. Data collection using Disaster Resilience questionnaires on Health Workers and DASS-21 (Depression Anxiety Stress Scale). The data analysis used in this study is univariate and bivariate. Spearman correlation is used to find out the relationship between the degree of closeness of two variables. Results from the Spearman Correlation Test show a significant relationship between disaster resilience with anxiety (R= -0,361, p value= 0.000) and weak correlation strength. It is hoped that the results of this study can be the next steps in improving the coping of health workers and providing policy recommendations related to the resources needed, as an informative reference not only for health workers but also for health students in formulating strategies to increase disaster resilience in health workers involved in disaster management.